Conditions Governing Food Protein Amyloid Fibril Formation—Part I: Egg and Cereal Proteins. Issue 4 (10th June 2019) - Jansens, Koen J.A.; Lambrecht, Marlies A.; Rombouts, Ine; Monge Morera, Margarita; Brijs, Kristof; Rousseau, Frederic; Schymkowitz, Joost; Delcour, Jan A.
Abstract: Conditions including heating mode, time, temperature, pH, moisture and protein concentration, shear, and the presence of alcohols, chaotropic/reducing agents, enzymes, and/or salt influence amyloid fibril (AF) formation as they can affect the accessibility of amino acid sequences prone to aggregate. As some conditions applied on model protein resemble conditions in food processing unit operations, we here hypothesize that food processing can lead to formation of protein AFs with a compact cross β‐sheet structure. This paper reviews conditions and food constituents that affect amyloid fibrillation of egg and cereal proteins. While egg and cereal proteins often coexist in food products, their impact on each other's fibrillation remains unknown. Hen egg ovalbumin and lysozyme form AFs when subjected to moderate heating at acidic pH separately. AFs can also be formed at higher pH, especially in the presence of alcohols or chaotropic/reducing agents. Tryptic wheat gluten digests can form fibrillar structures at neutral pH and maize and rice proteins do so in aqueous ethanol or at acidic pH, respectively.